Study on sound absorption performance of resonance structure for aluminum–polyurethane foam composite and plexiglass. Issue 3 (September 2022) - Yuan, Binxia; Fang, Xinyi; Liu, Jianben; Zhu, Rui; Cao, Lan
Low-frequency noise control in substations (converter stations) has received extensive attention. The sound absorption performance of a single material is limited. In the paper, aluminum–polyurethane (Al–PU) foam composite materials were prepared by impregnating method. The microstructure and composition of PU and Al–PU composite foam were characterized by scanning electron microscopy (SEM) and X-ray diffraction (XRD). The results showed that aluminum particles can be well adhered to the skeleton of PU foams, and the sound absorption coefficient of Al–PU foams at 50 Hz–315 Hz was greatly improved. Meanwhile, the resonance structures of Al–PU foams and plexiglass were further constructed. The sound absorption coefficient of different resonance structures was different, and the performance of the resonance structure with 10 mm back cavity and front hole was the best.